2015
DOI: 10.1007/s10803-015-2584-5
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Examination of Adaptive Behavior in Autism Spectrum Disorders: Influence of Executive Function

Abstract: This study characterizes longitudinal change in adaptive behavior in 64 children and adolescents with autism spectrum disorder (ASD) without intellectual disability (ID) evaluated on multiple occasions, and examines whether prior estimate of executive function (EF) problems predicts future adaptive behavior scores. Compared to standardized estimates for their developmental stage, adaptive behavior in most participants was impaired and did not improve over time. Prior EF predicted later adaptive behavior in dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
114
1
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(136 citation statements)
references
References 37 publications
13
114
1
8
Order By: Relevance
“…In contrast, none of the individual BRIEF scales significantly contributed to our models predicting functional communication or social skills among children with ASD, though for communication both the plan/organize and monitor scales approached significance. This is consistent with Wallace et al [] who found plan/organize to be a significant predictor of conceptual skills, and with Pugliese et al [], who identified that monitor significantly predicted communication scores. It may be that for both of these adaptive functioning domains, it is metacognitive abilities, collectively, that best translate into social and communicative competence, as opposed to proficiency within particular subdomains.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, none of the individual BRIEF scales significantly contributed to our models predicting functional communication or social skills among children with ASD, though for communication both the plan/organize and monitor scales approached significance. This is consistent with Wallace et al [] who found plan/organize to be a significant predictor of conceptual skills, and with Pugliese et al [], who identified that monitor significantly predicted communication scores. It may be that for both of these adaptive functioning domains, it is metacognitive abilities, collectively, that best translate into social and communicative competence, as opposed to proficiency within particular subdomains.…”
Section: Discussionsupporting
confidence: 91%
“…flexibility, problem-solving, planning) have shown much deficit in comparison to typical adults (Zimmerman et al, 2016) and similar deficits to those with attention deficit hyperactivity disorder (ADHD) conditions (Craig et al, 2016). Studies with adolescents and young adults also demonstrate that executive functioning impairments predict poor daily living skills (Pugliese et al, 2016). Yet, executive functioning is an often ignored target for treatment, and there are no known medications that correct most executive functioning deficits of AS.…”
Section: Remediating Executive Functioning and Social Deficits In Autismmentioning
confidence: 99%
“…Comorbid EF impairment is observed in 41% to 78% of cases (1), increases with age (2,3), and persists despite amelioration of ASD symptoms (4). This impairment in ASD spans component processes of EF (e.g., inhibition, shifting, working memory, planning/organization) (5), moderates defining ASD symptoms (6), and predicts worse adaptive functioning (7,8) as well as quality of life (3). Current hypotheses of ASD, which posit pathophysiology of network-level dysfunction, target core social-communicative symptoms (9), but leave open our understanding of comorbid executive dysfunction.…”
mentioning
confidence: 99%